Hospitallers and women in Scandinavia – mutual support - Jensen, Kurt Villads (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2023)
The Order of the Hospitallers had a privileged role in Scandinavia. In spite of this, only relatively few scholars have worked with the Order’s Scandinavian history, and none specifically with its relationships to women. The aim of the present article is to discuss women’s important role as donators and benefactors, what kind of agreements they could make of the Order, and the importance for the Order’s planning and expansion of estate.